Heritabilitas Cacing Heterakis gallinarum Asal Asia dan Eropa pada Ayam Lokal - Sunita, I Nyoman; Suratma, Nyoman Adi; Damriyasa, I Made (Buletin Veteriner Udayana, 2017)
The objective of this study is to evaluate the heritability of Heterakis gallinarum    originated from Asian and European in local chicken. Heritability was evaluated by rate and intensity of infection after inoculation of infective egg of the worms. In total of 32 local chickens were used in this study. Sixteen chicken were inoculated with infective egg of H. gallinarum originated from Asian and 16 other chicken were inoculated with infective egg of worms originated from Europa. All chicken were necropsed until 3 months in old.  The result of the study  showed that egg of H. gallinarum originataed from Asian developed in 10 local chicken (62,5%) and egg of worm originated from Europa in   15 (93,8%) of local chickens. The average numbers of H. gallinarum   originated from Asian and Europa were  9,75 ± 12,96 and 22,43 ± 20,45 worms respectively.  The defferences rate and intencity of infection in local chickens were inoculated with H. gallinarum from Asian and Europa indicated the difference of heritability of the worms.